2023
DOI: 10.1093/ejcts/ezad170
|View full text |Cite
|
Sign up to set email alerts
|

Paravertebral block combined with serratus anterior plane block after video-assisted thoracic surgery: a prospective randomized controlled trial

Abstract: Introduction Adequate pain management after thoracoscopic surgery is a major issue in the prevention of respiratory complications. The combination of the paravertebral block (PVB) with the serratus anterior plane block (SAPB) may decrease postoperative pain. The objective of this study was to evaluate the impact of the combination of PVB and SAPB on the consumption of morphine and pain after video or robot-assisted thoracic surgery (VATS or RATS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Another key finding was that the PVB + SAPB combination was not associated with lower postoperative pain level at PACU admission when compared with the single blocks alone. To date, only 1 randomized trial has measured the efficacy of the PVB + SAPB combination [ 21 ]. In contrast to our study, Dusseaux et al found that the PVB + SAPB combination was superior to PVB alone, with a significantly lower postoperative pain score 6 h after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another key finding was that the PVB + SAPB combination was not associated with lower postoperative pain level at PACU admission when compared with the single blocks alone. To date, only 1 randomized trial has measured the efficacy of the PVB + SAPB combination [ 21 ]. In contrast to our study, Dusseaux et al found that the PVB + SAPB combination was superior to PVB alone, with a significantly lower postoperative pain score 6 h after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These advantages seem comparable to the ones reported with the use of INB [ 71 ]. However, the combination of SAPB and PVB does not seem to provide better analgesia as compared to PVB alone [ 72 ]. Another advantage provided by SAPB is that it can be performed with the patient in a supine position, which aligns with the positioning required for robotic thoracic procedures, thereby streamlining the workflow [ 73 ].…”
Section: Serratus Anterior Plane Blockmentioning
confidence: 99%